The Hashtag #TaiwanCanHelp as a Strategy of Taiwan Warm Power Diplomacy - Eva Ermylina; Inda Mustika Permata (Sospol : Jurnal Sosial Politik, 2023)
This research intends to analyse diplomacy strategy using the hashtags #TaiwanCanHelp to enhance Taiwan’s “warm power” in the international community. This paper is qualitative-descriptive research and is analysed by using the concept of digital diplomacy. As a ghost island, Taiwan struggles to be present and seen in the international community. Taiwan’s success story in combating the COVID-19 pandemic has changed its global image. Taiwan has actively utilized this situation into political sentiment by campaigning the hashtags #TaiwanCanHelp on digital platforms to spreads its warm power and gain international recognition. The use of social media by government actors and activists has engaged awareness of Taiwan’s situation from more people. It was begun as a campaign to sound Taiwan’s exclusion from WHO and WHA, it later has been used as a slogan to construct Taiwan’s image in global presence as a warm, helpful, and friendly country.